ChemInform Abstract: Ag(I)‐Catalyzed Three‐Component Reaction of 2‐Alkynylbenzaldehydes, Amines, and Diazo Compounds. Issue 4 (January 2016) - Xiao, Tiebo; Peng, Pai; Xie, Yang; Wang, Zhao‐yang; Zhou, Lei
Abstract: A one‐pot three‐component cyclization of diazo compounds as nucleophiles with primary aromatic amines and alkynylbenzaldehydes gives 3‐benzazepines via a cascade imine—yne cyclization/nucleophilic addition/1, 2‐aryl migrations.